Explanation: The first step we need to take to find the answer is to find the value of y.
7(y+3)=5y+8 Expand the parentheses 7y+21=5y+8 Subtract both sides by 21 7y+21-21=5y+8-21 7y=5y-13 Subtract both sides by 5y 7y-5y=5y-13-5y 2y=-13 Divide both sides by 2 2y/2=-13/2 y=-6.5
Now, we plug y back into the original equation.
7(y+3)=5y+8 7(-6.5+3)=5(-6.5)+8 Expand the parentheses -45.5+21=-32.5+8 -24.5=-24.5
Because both sides of the equation is equal and the equation is true, we can conclude that the equation has one solution.